EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF FUTURE SPECIALISTS' TRAINING IN PHYSICAL REHABILITATION FOR SOCIAL ADAPTATION OF PUPILS WITH CEREBRAL PALSY - Світлана Шульце (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The effectiveness of the training of future specialists in physical rehabilitation for social adaptation of pupils with cerebral palsy is experimentally established. The components (motivative, semantic, procedural) and criterion of developed training. Pedagogical conditions of developed system implementation in the educational process of higher education, the focus of future specialists in physical rehabilitation self-assessment results for tools selection of social adaptation of pupils with cerebral palsy and comparison with experimental evaluation is grounded. The lowest result was observed in activity-component of students' readiness, indicating the need for the introduction of additional tools and methods for their preparation to study the activity.